1999
DOI: 10.1303/jjaez.43.181
|View full text |Cite
|
Sign up to set email alerts
|

Copulatory Behavior and Sex Pheromones in Sciarid Fly, Lycoriella mali (Fitch) (Sciaridae: Diptera).

Abstract: The mating behavior of the sciarid fly, Lycoriella mali, a serious insect pest of mushroom cultivation in Japan, was analyzed for the presence of sex pheromones. Unmated male flies made copulatory responses, such as wing fanning, ventral bending of abdomen and opening of clasper, to an unmated female, crude extracts of an unmated female and separate body parts of an unmated female, suggesting the presence of female sex pheromones on all parts of female flies. However, unmated male flies did not make any copula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Lycoriella mali (Fitch 1856), Kostelc et al. (1980) reported n‐heptadecane as major attractant of the female sex pheromone, but this result could not be confirmed in a more recent study (Gotoh et al. 1999).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Lycoriella mali (Fitch 1856), Kostelc et al. (1980) reported n‐heptadecane as major attractant of the female sex pheromone, but this result could not be confirmed in a more recent study (Gotoh et al. 1999).…”
Section: Introductionmentioning
confidence: 89%
“…In Lycoriella ingenua (Dufour, 1839) syn. Lycoriella mali (Fitch 1856), Kostelc et al (1980) reported n-heptadecane as major attractant of the female sex pheromone, but this result could not be confirmed in a more recent study (Gotoh et al 1999). In sciarid males, the female extract evokes attraction, characteristic courtship behaviour including wing fanning and grasping the abdominal tip of the female with the claspers.…”
Section: Introductionmentioning
confidence: 93%
“…Uit een studie van Sonoda et al (2014) Alhoewel voor verschillende soorten rouwmuggen bekend is dat de vrouwtjes sexferomonen produceren (e.g. Alberts et al 1981, Gotoh et al 1999, Liu et al 2002, Frank and Dettner 2008, zijn deze sexferomonen nog niet chemisch gekarakteriseerd. Er zijn geen lokstoffen bekend die de oevervlieg S. tenuicosta aantrekken en ook zijn er geen studies gedaan naar (sex)feromonen in oevervliegen.…”
Section: Herkenning En Levenscyclus Van Oevervliegenunclassified
“…Brdysia paupera B. agrestis Lycoriella mali 1985Lycoriella mali , 1993Lycoriella mali 1993Lycoriella mali , 19971999 fungus gnats Cantelo, 1989;King, 1991Brewer, 1990Bartlett andKeil, 1997 1995;1995BT Osborne et al, 1985Gouge and Hague, 1994;Hellqvist, 1994;Wright and Chambers, 1994;Ydergaard et al, 1997Ydergaard et al, 1997Jess and …”
Section: Finmentioning
confidence: 99%